Comparative analysis of cytokine profiles in gingival crevicular fluid of subjects with metal-ceramic and all-ceramic fixed dental prostheses: Analisis perbandingan profil sitokin cairan sulkus gingiva pada subjek prostesis metal-keramik dan all-keramik - Jubhari, Eri Hendra; Chandra, Andi Ayodhya (Makassar Dental Journal, 2025)
This article analyses the comparison of inflammatory cytokine profiles in gingival crevicular fluid (GSF) in subjects using metal-ceramic and all-ceramic fixed dentures; through a literature review with data collection from various related studies. The study re-sults indicate that metal-ceramic prostheses tend to elicit higher levels of inflammatory mediators, such as IL-1β, IL-6, and TNF-α, compared to all-ceramic prostheses. These differences are associated with the surface characteristics of the materials and the level of prosthesis margin adaptation. It was concluded that the choice of prosthesis material significantly influences the inflam-matory response of periodontal tissue, so all-ceramic materials with CAD/CAM technology are more recommended for main-taining long-term periodontal health.